TATA KELOLA ASET DAERAH KOTA PEKANBARU TAHUN 2017 - Oktavia Sudiana Ningsih; Hasanuddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Regional asset management is a series of processes involving three state actors including the government, the private sector and the community. Furthermore, to see good governance of regional assets, it needs to be measured through the principles of good governance, which include the principles of participation, transparency, accountability and the principles of effectiveness and efficiency.This research was conducted with the aim of describing Asset Governance in 2017. This research is a descriptive study with a qualitative approach. The location of this research was conducted at the Regional Financial and Asset Management Agency (BPKAD) Pekanbaru City. Data collection techniques used are interviews and documentation. The data analysis technique used is descriptive and qualitative methods.The results of this study indicate that the regional asset management of Pekanbaru city still needs to pay attention to several stages of asset management. Even though the city of Pekanbaru in 2017 has won a WTP (Unqualified) opinion, in fact the city of Pekanbaru still has problems in asset security, asset inventory, write-off and asset administration. This can be seen from the results of measurements through the principles of good governance that there are still many things that need to be considered by the regional asset manager of the city of Pekanbaru in the sense of BPKAD for the city of Pekanbaru to be even better. Keywords: governance, good governance